MOLECULAR ANALYSIS OF MLL GENE REARRANGEMENTS IN CHILDHOOD ACUTE LEUKEMIA: A HOSPITAL BASE STUDY: Life Science - Pathology - MOJTABA HOSEINIHAROUNI, SEYED; MOTEVASELI, ELAHE; ROSTAMI, SHAHRBANO; CHAHARDOULI, BAHRAM; HOSSEIN MODARRESSI, MOHAMMAD (International Journal of Life Science and Pharma Research, 2018)
Acute leukemia (AL) is one of the most common hematologic malignancies in children. Acute leukemia characterized by several genetics changes which could affect patient’s prognosis. Chromosomal rearrangements involving MLL gene have been associated with dismal outcome in acute leukemias. The present study projected to detect the six most frequent MLL fusion transcripts in Iranian childhood acute leukemia patients. Peripheral blood (PB) and bone marrow (BM) samples of 115 pediatric (one month to 15 years) newly diagnosed AL patients were subjected for molecular analysis. Written consent was obtained from the patient’s parents. Paired multiplex reverse-transcriptase polymerase chain reaction (PMRT-PCR) technique was performed for molecular analysis. Only 16.4% of cases were AML. Disease recurrence was seen in 16.4%. Regard to vital status 82.6% of cases was alive. Obtained results revealed 2.6% MLL rearrangement positive in samples.MLL rearrangement negative had longer OS. Quantitative RT-PCR assay of MLL revealed a down regulation in 44% patients. Data analysis shows no correlation between MLL gene expression and CBC indices. In relation to obtained data it concluded that multiplex PCR as a sensitive molecular technique is willing to come in routine molecular labs